Case load and valve surgery outcome in Australia. (15th October 2016) - Russell, E. Anne; Baker, Robert A.; Bennetts, Jayme S.; Brown, Alex; Reid, Christopher M.; Tam, Robert; Tran, Lavinia; Walsh, Warren F.; Maguire, Graeme P.
Abstract: Background: In Australia it has been suggested that heart valve surgery, particularly for rheumatic heart disease (RHD), should be consolidated in higher volume centres. International studies of cardiac surgery suggest large volume centres have superior outcomes. However the effect of site and surgeon case load on longer term outcomes for valve surgery has not been investigated. Methods: The Australian and New Zealand Society of Cardiac and Thoracic Surgeons Cardiac Surgery Database was analysed. The adjusted association between both average annual site and surgeon case load on short term complications and short and long-term survival was determined. Results: Outcomes associated with 20, 116 valve procedures at 25 surgical sites and by 93 surgeons were analysed. Overall adjusted analysis showed increasing site and surgeon case load was associated with longer ventilation, less reoperation and more anticoagulant complications. Increasing surgeon case load was also associated with less acute kidney injury. Adjusted 30-day mortality was not associated with site or surgeon case load. There was no consistent relationship between increasing site case load and long term survival. The association between surgeon case load and outcome demonstrated poorer adjusted survival in the highest volume surgeon group. Conclusions: In this Australian study, the adjusted association between surgeon and site case load was not simple or consistent. Overall larger volume sites or surgeons did not have superior outcomes. Mandating a particular site case load level for valve surgery or a minimum number of procedures for individual surgeons, in an Australian context, cannot be supported by these findings.